Analysis of Computer Based Design in Architectural and Convectional Drafting Methods in Schools. The Case of Auchi Polytechnic, Auchi (Global Journal of Human-Social Science, 2019)
The paper compares the concepts of computer-aided design in architecture (CAAD) to manual drafting (MD) in Auchi Polytechnic, Auchi. These techniques are educational tools designed to train the student to become better in project design and creativity. A structurallybased questionnaire was developed to measure a series of active variables of CAAD and MD. The results revealed that ninety percent (90%) of the HND students indicated a strong preference for CAAD while most of the OND students were not aware of CAAD software. AutoCAD architecture is mostly taught at the Department and the students generally prefer to use Revit Software for their studio and design project. It is realized that the students are highly interested in learning and applying CAAD in the studio and project design; having discovered that CAAD proficiency through self-learning approach was estimated to be the highest out of the five considered techniques.
Keywords: computer-aided design in architecture; manual drafting; educational tools; curriculum